A Gated Recurrent Unit Aided Lee-Carter Model for mortality projection (Journal of Pure and Applied Sciences (Science Forum), 2023)
Over the past decades, new models for mortality modelling have been developed. Apioneering and one of the most influential model, among others, is the Lee-Carter(LC) model, developed by Lee and Carter in 1992. The method traditionally used inthe LC model shows obvious drawback in describing the shape of future mortality.This work used a more robust approach based on a deep learning technique thatdiffers from the literature. More precisely, a Gated recurrent unit (GRU) wasintegrated with the Lee–Carter model to increase its capacity for prediction. The LC-GRU model performs well in terms of predicted accuracy. The strength of the gatedrecurrent unit network lies in its capability to handle the non-linearity inherent inmortality data and long-term dependencies in time series data. The research resultsshows that the LC-GRU model has minimum errors and thus performs better thanthe LC model.